2014
DOI: 10.1159/000359955
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Procedural Variants in Cognitive-Behavioral Therapy: A Randomized, Controlled Multicenter fMRI Study

Abstract: Background: Cognitive behavioral therapy (CBT) is an effective treatment for panic disorder with agoraphobia (PD/AG). It is unknown, how variants of CBT differentially modulate brain networks involved in PD/AG. This study was aimed to evaluate the effects of therapist-guided (T+) versus self-guided (T-) exposure on the neural correlates of fear conditioning in PD/AG. Method: In a randomized, controlled multicenter clinical trial in medication-free patients with PD/AG who were treated with 12 sessions of manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 84 publications
0
20
0
1
Order By: Relevance
“…Importantly variation in HTR1A is not related ( P >0.2) to treatment variants (therapist vs self-guided exposure), which has been previously shown to be related to exposure behaviour 35 and the neural correlates of conditioning. 50 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly variation in HTR1A is not related ( P >0.2) to treatment variants (therapist vs self-guided exposure), which has been previously shown to be related to exposure behaviour 35 and the neural correlates of conditioning. 50 …”
Section: Resultsmentioning
confidence: 99%
“…For detailed information of the clinical and treatment aspects of the study, please see Gloster et al 35 , 45 and Straube et al 46 Sessions 1–3 consisted of psychoeducation and an individualized behavioural analysis of the patient's symptoms and coping behaviours. Sessions 4–5 provided the treatment rational for exposure and implemented interoceptive exposure exercises in the therapy room identically for both groups.…”
Section: Methodsmentioning
confidence: 99%
“…During acquisition, greater differential activation of IFG has been seen in PD/A patients versus controls (Lueken et al, 2014), and cognitive behavioral therapy (CBT) reduced this activation in PD/A patients (Kircher et al, 2013). Further studies found that PD/A patients receiving CBT treatment also showed greater activation of the hippocampus during fear acquisition, and this was positively correlated with treatment outcome (Lueken et al, 2013;Straube et al, 2014a). These studies also found that CBT treatment is associated with lowered connectivity between the left IFG and the left hippocampus across time.…”
Section: Panic Disordermentioning
confidence: 99%
“…Viele dieser Studien sind innerhalb der großen Multizenterstudie Panik-Netz durchgeführt worden [43]. Veränderungen regionaler Aktivierungen und Konnektivitätsmuster in Verbindung mit Psychotherapieeffekten werden für Amygdala, Mittelhirn, Hippocampus, ACC und frontale Regionen beschrieben, was weitgehend mit dem beschriebenen Furchtnetzwerk überlappt (für Effekte einer psychodynamischen Therapie [44], für Effekte in einem Konditionierungsparadigma [33,45]; für eine Übersicht [46].…”
Section: Therapiestudienunclassified